Further Development of Small Hydropower Facilities May Alter Nutrient Transport to the Pantanal Wetland of Brazil - Oliveira, Marcia Divina de; Fantin-Cruz, Ibraim; Campos, Juliana Andrade; Campos, Marcel Medina de; Mingoti, Rafael; Souza, Marcelo Luiz de; Figueiredo, Daniela Maimoni de; Dores, Eliana Freire Gaspar de Carvalho; Pedrollo, Olavo; Hamilton, Stephen K. (Frontiers in Environmental Science, 2020)
Small hydropower (SHP) facilities are the most common kind of hydroelectric dams being built around the world, and although they are generally viewed as less environmentally harmful than larger dams, there has been little research to support that assertion, particularly in tropical and subtropical regions where the most new SHPs are being constructed. Numerous SHPs have been built, and many more are in development or proposed, in rivers that drain into the Pantanal, a world-renowned floodplain wetland system located mostly in Brazil. The upland tributaries transport sediments and nutrients into the Pantanal, thereby affecting the geomorphological dynamics and biological productivity of downstream floodplains. This study presents measurements from upstream and downstream of 25 current hydropower facilities, most of which are SHPs, throughout the upland watersheds of the Upper Paraguay River basin to reveal how these facilities may affect the concentrations and transport of nutrients in rivers flowing to the Pantanal. In addition, a predictive model using artificial neural networks estimates the impact of building 80 future SHPs on nutrient transport into the Pantanal, based on observations at current facilities as well as the spatial distribution of future facilities. Overall impacts of current hydropower facilities were not large, and in many cases were indistinguishable based on comparisons between upstream and downstream. The short water residence times of reservoirs associated with SHPs likely explain their tendency to have little or no effect on nutrient transport. However, model predictions for hydropower facilities that may be built in the future, many on rivers with higher discharge and sediment loads, point to significant reductions in overall TN (8%) and TP (29%) transport, with potential negative consequences for river and floodplain productivity. Negative impacts may be either because the rivers carry low nutrient concentrations and are thereby sensitive to oligotrophication, or they are particularly important overall nutrient sources supporting ecosystem productivity in downstream rivers and floodplains. These results support recommendations that several river systems presently lacking dams in their lower reaches should be excluded from future hydropower development to maintain the nutrient supply to the Pantanal.